2016
DOI: 10.18632/oncotarget.9185
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CHK1 enhances cell death induced by the Bcl-2-selective inhibitor ABT-199 in acute myeloid leukemia cells

Abstract: Resistance to standard chemotherapy agents remains a major obstacle for improving treatment outcomes for acute myeloid leukemia (AML). The Bcl-2-selective inhibitor ABT-199 has demonstrated encouraging preclinical results, drug resistance remains a concern. Mcl-1 has been demonstrated to contribute to ABT-199 resistance, thus combining with therapies that target Mcl-1 could overcome such resistance. In this study, we utilized a CHK1 inhibitor, LY2603618, to decrease Mcl-1 and enhance ABT-199 efficacy. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…This is consistent with reports that in solid tumors, including melanoma, HLA-DR signaling is through phosphorylation of p125 focal adhesion kinase and not ERK (2,30). In AML, it has been suggested that increased expression of Bcl-2 proteins, in particular Mcl-1, act to attenuate apoptosis (35,36). Using drugs that induce DNA damage decreased levels of Mcl-1 and increased apoptosis in AML cells (36).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with reports that in solid tumors, including melanoma, HLA-DR signaling is through phosphorylation of p125 focal adhesion kinase and not ERK (2,30). In AML, it has been suggested that increased expression of Bcl-2 proteins, in particular Mcl-1, act to attenuate apoptosis (35,36). Using drugs that induce DNA damage decreased levels of Mcl-1 and increased apoptosis in AML cells (36).…”
Section: Discussionsupporting
confidence: 89%
“…In AML, it has been suggested that increased expression of Bcl-2 proteins, in particular Mcl-1, act to attenuate apoptosis (35,36). Using drugs that induce DNA damage decreased levels of Mcl-1 and increased apoptosis in AML cells (36). Because IMMU-140 is capable of inducing significant damage to DNA in targeted cells through its SN-38 payload, including in AML, it is possible that an added benefit of IMMU-140 is to make targeted AML cells more sensitive to the direct signaling activity mediated by HLA-DR.…”
Section: Discussionmentioning
confidence: 99%
“…MOLM‐13 was purchased from AddexBio (San Diego, CA, USA). The cell lines were cultured as previously described, and were authenticated in August 2017 at the Genomics Core at Karmanos Cancer Institute using the PowerPlex ® 16 System from Promega (Madison, WI, USA). The cell lines were tested for the presence of mycoplasma by PCR on a monthly basis …”
Section: Methodsmentioning
confidence: 99%
“…MTT (3‐[4,5‐dimethyl‐thiazol‐2‐yl]‐2,5‐diphenyltetrazoliumbromide; Sigma‐Aldrich) assays were performed as previously described . Human PMNC samples were treated with variable concentrations of ABT‐199 and/or KPT‐330 for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao J. and colleagues have recently reported the efficacy of LY2603618 in combination with the BCL-2 inhibitor ABT-199 in AML cell lines and primary cells ( n  = 26). The authors demonstrated that the treatment with LY2606368 reduced the total amount of MCL-1 and, consequently, enhanced the efficacy of ABT-199 in terms of induction of apoptosis [101]. …”
Section: Introductionmentioning
confidence: 99%